Ethnobotanical Study of Komak Plants in East Lombok Regency - Handayani, Agustia Fitri; sukiman, sukiman; Sukenti, Kurniasih; Julisaniah, Nur Indah; Kurnianingsih, Rina (Samota Journal of Biological Sciences, 2024)
Indonesia is a country that has a high level of diversity, with fertile soil so various types of plants can grow well, such as beans. One of the Leguminosae that has the potential to be cultivated as a vegetable, protein source and animal feed is the komak plant. East Lombok Regency is part of West Nusa Tenggara Province which has a number of areas that produce komak plants which are quite high, but information on their utilization is still limited. This study aims to determine the diversity of species and morphology of the komak plant, utilization, and cultivation of the komak plant based on local knowledge of the people in East Lombok Regency. The research was conducted in several sub-districts in East Lombok Regency from August 2021 to June 2022. This research used the Purposive sampling and Snowball sampling with semi-structured interviews. The results of this study found 3 species of komak plants namely Lablab purpureus (L) Sweet (which consists of 3 variants Lablab purpureus subsp. purpureus, Lablab purpureus var. typicus and Lablab purpureus var. lignosus), Phaseolus lunatus L. and Canavalia ensiformis (L.) DC. Various uses of komak as food, animal feed, land border, shade, hair fertilizer and traditional events. Lablab purpureus subsp. purpureus is the most important type of komak with an ICS value of 27 which is used in almost all types of utilization. Community knowledge in East Lombok Regency in cultivating komak plants is quite good starting from seed preparation, planting process, maintenance and harvesting of komak plants.